Teacher self-efficacy in online education: a review of the literature - Michael Corry; Julie Stella (Association for Learning Technology, 2018)
Although empirical validation of teacher self-efficacy in face-to-face environments continues, it remains a relatively new construct in online education. This literature review, which was conducted over academic databases and which examined work published in the past 15 years, explores three areas of research about teacher self-efficacy in online education: (1) ease of adopting online teaching, (2) online teaching self-efficacy in comparison to demographic and experience variables and (3) changes in teacher self-efficacy in professional development scenarios where self-efficacy was measured before and after treatment. Research studies demonstrate agreement (or no discernible disagreement) in the importance of system/curriculum quality in the implementation of online learning and the recognition that a measure of self-efficacy in online pedagogy has not yet been empirically derived. Researchers continue to examine the balance of technological and pedagogical knowledge that supports the development of teacher self-efficacy, the role of learner self-efficacy in teacher self-efficacy and whether teacher self-efficacy differs fundamentally in online education. In addition, it seems clear that empirical validation of the association of teacher self-efficacy and student success has yet to occur in online education with the rigour seen in face-to-face modes of delivery.